EFFECT OF PRE AND POST EMERGENCE HERBICIDES ON WEED DYNAMICS IN ONION (Allium cepa L.) CV.N-53 - K.SASIKALA, M.VENKATESWARA REDDY,K.UMAJYOTHI, P.SYAM SUNDAR REDDY and (The Journal of Research, PJTSAU, 2017)
A field experiment was conducted to find out best weed management practices in onion (Allium cepa L.,) during rabi 2011-12 and 2012-13. The experiment was laid out in Randomized block design with three replications.Weed population, weed dry matter , weed control efficiency and weed index were significantly influenced by weed management practices. Weed population and weed dry matter accumulation were significantly reduced with application of pre emergence herbicides coupled with Quizalofop ethyl @ 75 g a.i / ha as post emergence application (20 DAT) compared with weedy check during both the years of investigation. Application of pendimethalin and oxyflourfen supplemented with Quizalofop ethyl @ 75 g a.i / ha as post emergence found to be as good as hand weeding thrice on bulb yield and weed dynamics. Though Imazethapyr @ 100 g a.i / ha as post emergence application (20 DAT ) effectively controls the weeds and reduces weed dry matter compared to weedy check but poor yield was recorded due to extremely phytotoxic to the Onion.